2018
DOI: 10.1080/08897077.2018.1439802
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Pharmacological Or Psychological Interventions for Smoking Cessation in Smokers with Major Depression Or Depressive Symptoms: A Systematic Review of the Literature

Abstract: More research is needed into effectively addressing smoking in people with concurrent mental disorder. Data currently available need to be confirmed in randomized trials aimed at replicating the results and disentangling the effects of each therapeutic ingredient when a combination therapy is proposed. Studies on tolerability of treatments are warranted, as well as those aimed at identifying factors of vulnerability to adverse effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 62 publications
(179 reference statements)
1
4
1
Order By: Relevance
“…Our findings were consistent with previous studies that found an association between receiving services for tobacco/nicotine use and nicotine dependence remission (Aldi et al, 2018; Annamalai et al, 2015; Rüther et al, 2014; Stubbs, Vancampfort, Bobes, De Hert, & Mitchell, 2015). In addition, the current study extends the prior research with population‐based data.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our findings were consistent with previous studies that found an association between receiving services for tobacco/nicotine use and nicotine dependence remission (Aldi et al, 2018; Annamalai et al, 2015; Rüther et al, 2014; Stubbs, Vancampfort, Bobes, De Hert, & Mitchell, 2015). In addition, the current study extends the prior research with population‐based data.…”
Section: Discussionsupporting
confidence: 93%
“…This might be partially related to the health care providers' lack of knowledge of effective programs and tobacco/nicotine use treatment strategies for those with SMI (Missen, Brannelly, & Newton‐Howes, 2013; Rae, Pettey, Aubry, & Stol, 2015). However, evidence from clinical trials suggests that pharmacological services alone or combined with behavioral and psychological support is effective for tobacco/nicotine use and tolerated by smokers with SMI (Aldi, Bertoli, Ferraro, Pezzuto, & Cosci, 2018; Anthenelli et al, 2013; Dubrava & Anthenelli, 2018; Hall et al, 2006; Secades‐Villa, González‐Roz, García‐Pérez, & Becoña, 2017; Tidey & Rohsenow, 2009; Tsoi, Porwal, & Webster, 2013; Williams et al, 2012)…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other aspects could have contributed to these results, such as the use of medications, morbidities, and the period of follow-up. The first-line pharmacological treatment for smoking cessation in most countries is varenicline and nicotine replacement combined with cognitive-behavioural therapy, the combination of therapies are more effective than isolated drugs in smokers, with depression and smokers with chronic obstructive pulmonar disease [54][55][56] . www.nature.com/scientificreports/…”
Section: Discussionmentioning
confidence: 99%